Towards a service-oriented Middleware Enabling Context Awareness for Smart Environment. (10th December 2008) - Bai, Yuebin; Ji, Haixing; Han, Qingmian; Huang, Jun; , Zhiyuan Zhang
To screen heterogeneity of sensor hardware and support rapid development of applications in context-awareness, the idea of middleware is widely adopted. In this paper, the middleware is proposed to support the application development of context-awareness under ubiquitous networks environment. It applies the updated service-oriented and light-weight structure with excellent expansibility and efficiency in the running process. The architecture of middleware is presented and described in detail. Running structure of the middleware is proposed. At the end of the paper, a healthcare scenario is used to validate the design methodology and demonstrate the supporting function of middleware.